Musculoskeletal disorders and associated factors in nurses and bank workers in South Africa - Nyantumbu-Mkhize, Busisiwe Maria (My University, 2017)
Background Work has long been suspected of being involved in the genesis of musculoskeletal disorders. These disorders have been found to affect a significant proportion of the working population. Certain occupational groups across different industries are at a particular risk of musculoskeletal disorders possibly, due to the nature of their work, including nurses and bank workers. In South Africa, there is a paucity of information regarding musculoskeletal disorder risk factors in these two occupational groups. Additionally, no follow-up studies have been conducted to examine incident (new onset) and persistent pain and socio-cultural factors potentially associated with musculoskeletal pain. The research reported in this thesis was conducted in public hospital nurses and call centre bank workers. Objectives  To determine the 12-month prevalences and body site localisation of reported musculoskeletal disorders in South African public hospital nurses and bank workers.  To characterise the features and consequences of prevalent musculoskeletal disorders in South African public hospital nurses and bank workers.  To identify the risk factors associated with prevalent musculoskeletal disorders in South African public hospital nurses and bank workers.  To determine incident and persistent musculoskeletal disorders in South African public hospital nurses.  To identify the risk factors associated with persistent musculoskeletal disorders in South African public hospital nurses. Methods The study had a baseline cross-sectional component which included both nurses and bank workers and a follow-up component ranging from 11.2-13.0 months from baseline which covered nurses. The main data collection tools were the modified CUPID baseline and follow-up questionnaires which were composites of standardised and validated instruments. Since the questionnaires were written in English, the baseline questionnaire was piloted in a suitable group of workers not earmarked for the study, for clarity and comprehension of questions and the time it would take to administer one questionnaire. After making the necessary changes, the baseline questionnaire was administered through interviews to 488 South African workers comprising 252 nurses and 236 bank workers who provided informed consent to participate in the study. Information about demographic characteristics, potential musculoskeletal disorder risk factors and occurrence of musculoskeletal disorders and their associated consequences was collected. At follow-up, 189 nurses (75.3%) who had participated at baseline were successfully re-interviewed about the occurrence of musculoskeletal disorders a month before the follow-up period. The collected data were cleaned and prepared for analysis. Descriptive statistics were generated followed by the selection of explanatory variables to be included in the multiple logistic regression. These variables were used to build partial models with age group, sex and occupational group. Variables with p-values ≤ 0.2 were viii selected for the full models. The full models were run to produce final models which contained variables with p-values < 0.05. Results Prevalence and characteristics of musculoskeletal disorders in South African workers, public hospital nurses, and bank workers The estimated 12-month prevalences (95% CI) of musculoskeletal disorders reported by the South African workers, public hospital nurses, and bank workers were high at 80.5% (77.0%-84.0%), 84.1% (79.5%-88.6%) and 76.7% (71.3%-82.1%), respectively. The most prevalent pain was in the low back (56.9%, 58.2% and 55.5%) and the least prevalent in the elbows (14.3%, 13.2% and 15 7%). More than half (58.6%, 64.9% and 51.4%) of the workers who reported pain in different body sites consulted healthcare providers for pain. Conservative estimates of sick leave days taken by each worker in the past 12 months due to musculoskeletal disorder pain were 2.2, 2.4 and 1.9 days for all workers, nurses and bank workers, respectively. Risk factors for musculoskeletal disorders in South African workers, public hospital nurses and bank workers Somatising tendency In South African workers, somatising tendency was associated with the reporting of pain in all body sites considered in the study. The associations with pain in “any” body site ORs (95% CI) 2.23 (1.15-4.31); 3.52 (1.84-6.72) and low back 1.81 (1.07-3.03); 2.72 (1.69-4.40), demonstrated increasing trends when the effect of one and two distressing somatic symptoms was compared to no symptoms, respectively. In public hospital nurses, it was associated with pain in four body sites which included “any” body site 6.58 (1.76-24.47) and knees 2.80 (1.33-5.86) and in bank workers, in six body sites which included “any” body site 3.17 (1.40-7.19) and low back 2.56 (1.22-5.36) when the effect of two or more distressing somatic symptoms was compared to no symptoms. Sex “Women” in South African workers and bank workers was associated with pain in the upper limbs constituted by shoulders 1.83 (1.04-3.37); 1.90 (1.01-3.59) and wrists or hands 2.28 (1.09-4.74); 2.53 (1.11-5.75) compared to men, respectively. Age group In South African workers, age groups (40-49 and ≥50 years) demonstrated increasing trends with pain in the shoulders 2.23 (1.27-3.90); 2.40 (1.21-4.79) and knees 2.18 (1.16-4.09); 2.50 (1.16-5.38), respectively. In public hospital nurses, age group (40-49 years) was associated with pain in the shoulders 4.70 (1.15-19.10) and age group (≥50 years) with pain in “any” body site 2.67 (1.09-6.54). In bank workers, an increasing trend with age groups (40-49 and ≥50 years) was demonstrated with pain in the knees 2.91 (1.19-7.10) and 4.04 (1.32-12.38), respectively. The effect of each age group was compared to <30 years age group. Occupational group Occupational group (bank workers) was associated with pain in the neck 1.66 (1.04-2.67) but no positive association was found with pain in “any” body site 0.51 (0.27-0.96) compared to nurses. Incident and persistent musculoskeletal disorders in public hospital nurses Incident “any” musculoskeletal disorders (95% CI) were estimated at 47.6% (36.5%-58.6%) with incident low back pain affecting the largest percentage of nurses (32.8%) and incident elbow pain (8.5%) the lowest. Persistent “any” musculoskeletal disorders (95% CI) were estimated at 83.7% (76.2%-91.1%) with persistent knee pain affecting most nurses (71.4%) and persistent elbow pain the least number of nurses (36.4%). Risk factor for persistent musculoskeletal disorders in public hospital nurses Somatising tendency was associated with persistent pain in “any" body site 7.32 (1.34-39.88) when the effect of two or more distressing somatic symptoms was compared to no symptoms. Ethnicity Ethnic group was associated with wrists or hands and low back. In all workers, Nguni and “other” ethnic groups were associated with wrists or hands 1.85 (1.08-3.18); 2.02 (1.09-3.72) and in bank workers 3.75 (1.41-9.97); 2.87 (1.13-7.28), respectively. In nurses, the “other” ethnic group was associated with wrists or hands 2.81 (1.07-7.39). In all workers, “other” ethnic group was associated with low back 1.86 (1.07-3.34) and in bank workers 2.43 (1.16-5.08). The effect of ethnic groups was compared to the Sotho group. Conclusions The study found a high burden of musculoskeletal disorders in the two groups of workers studied with pain in the low back being the most prevalent. The large proportions of workers, who consulted healthcare providers and took time off from work due to musculoskeletal disorders, indicate the negative impact that these disorders may have on the affected workers and their places of work. The main risk factors emerging from this research belong to the individual dimension of musculo-skeletal disorder risk factors. This may signal their importance in the development and persistence of these disorders. Furthermore, they may need to be considered in any effort to address musculoskeletal disorders in the groups of workers studied. This study failed to provide convincing evidence of association between ethnicity and musculoskeletal disorders in the groups studied.
A thesis submitted to the faculty of Health Sciences, University of Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg, 2017
Keywords: Musculoskeletal Diseases